Scaredycrow - Hernandez, Christopher; Poling, Kyle (New York, N.Y. : Scholastic Inc., 2013)
In a corn field stands a scarecrow called Scaredycrow who is as afraid of all the animals he sees as they are afraid of him--but one little brown field mouse is not scared.
Accelerated Reader AR
Keywords: Scarecrows -- Juvenile fiction; Mice -- Juvenile fiction; Fear -- Juvenile fiction; Friendship -- Juvenile fiction